THE EFFECT OF OF CLIMATE ORGANIZATIONS,CAREER DEVELOPMENT AND COMPENSATION TOWARD THE PERFORMANCE OF EMPLOYEES IN PT. EXERTAINMENT INDONESIA MEDAN - Prayogoi, Angga Surya (Universitas Harapan Medan, 2023)
This research was conducted at PT. Exertainment Indonesia Medan by focusing on the influence of organizational climate, career development and compensation toward employee performance. The purpose of this study to determine and analyze the partial effect and simultaneous organizational climate variables, career development and compensation to employees performance at PT. Exertainment Indonesia Medan. This type of research is associative. The study population that employees working at PT. Exertainment Indonesia Medan as many as 75 people so the sample using saturated samples (census) by 75 respondents. Sources of data research using primary data and data collection using survey techniques. Data were analyzed using multiple linear regression. Based on the results of the study showed that partially organizational climate have influence positive and significantly toward employee performance, career development have positive but not significant effect on employee performance and compensation have positive but not significant effect on the performance of employees at PT. Exertainment Indonesia Medan. The coefficient of determination (adjusted R2) of 0.547 means the performance of employees at PT. Exertainment Indonesia Medan was able to be explained by the organizational climate, career development and compensation amounting to 54.70% and the remaining 45.30% was able to be explained by other variables outside the scope of the research was not done.